Burundi : Joint Staff Advisory Note of Poverty Reduction Strategy Paper Preparation Status Report. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
The Joint Staff Advisory Note (JSAN) of the Poverty Reduction Strategy Paper (PRSP) Preparation Status Report (PSR) on Burundi explains progress in developing the full PRSP as set out in the PSR. The PSR describes the actions that have been taken, or are under way, with the support of technical assistance, to improve the information base on the prevalence, characteristics, and perceptions of poverty in Burundi. The PSR also describes the considerable progress that has been achieved in improving the government's capacity to monitor and evaluate public social expenditures and other poverty-reducing outlays.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: CR; I-PRSP Framework; ISCR; PRSP Preparation Status Report; PRSP Process; Burundi